2014
DOI: 10.5815/ijitcs.2014.08.09
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Diffusion Load Balancing Algorithm in Distributed System

Abstract: Abstract-In distributed computing system some nodes are very fast and some are slow and during the computation many fast nodes become idle or under loaded while the slow nodes become over loaded due to the uneven distribution of load in the system. In distributed system, the most common important factor is the information collection about loads on different nodes. The success of load balancing algorithm depends on how quickly the information about the load in the system is collected by a node willing to transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been shown that as more information is collected by an algorithm, the algorithm can make better load balancing decisions however at an increased overhead [16]. Dynamic load balancing technique is opted for heterogeneous systems in computational grids because the technique considers nodes with different processing speeds and memory sizes, bandwidth and load [16].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that as more information is collected by an algorithm, the algorithm can make better load balancing decisions however at an increased overhead [16]. Dynamic load balancing technique is opted for heterogeneous systems in computational grids because the technique considers nodes with different processing speeds and memory sizes, bandwidth and load [16].…”
Section: Related Workmentioning
confidence: 99%
“…Rafiqul and Ali proposed a diffusion load balancing algorithm for distributed computing systems [16]. They have shown that the communication overhead depends on the load of the nodes.…”
Section: Related Workmentioning
confidence: 99%
“…In cloud computing, load balancing refers to the distribution of client requirements across multiple application servers operating in the cloud background. Cloud load balancing, aided by various types of load balancers, significantly enhances application performance and reliability [1]. The advantages of dispersing resources from typical local sources often involve cost reduction and meeting demand more efficiently [2].…”
Section: Introductionmentioning
confidence: 99%
“…• Distributes incoming traffic across multiple computational resources Load balancing significantly improves global system performance in terms of throughput and resource utilization. The several reasons to use LBAs are as follows: cost optimization, fault tolerance ability, system adaptability and extensibility, decreased response time, idle time of resources, increased throughput, reliability, and starvation prevention [1,2].…”
Section: Introductionmentioning
confidence: 99%